Angioedema in Systemic Lupus Erythematosus (SLE) in Emergency Setting: A Case Report - Nur Mujaddidah Mochtar; Ricky Indra Alfaray; Detty Irawaty; Yelvi Levani (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
AbstractSystemic Lupus Erythematosus (SLE) is an autoimmune disease which causes chronic inflammation with its characteristics of the formation of autoantibody that attacks nuclear antigen. This disease may damage multisystem organs, and its diagnoses are barely implemented in the Emergency Department. However, cases of angioedema on SLE patient are quite uncommon not only in Indonesia but also globally. This article report an interesting case of 20 years old woman who came to the Emergency Department of Siti Khodijah Sepanjang Hospital with a complaint of swollen lips for three days. The complaint and examination led to the diagnosis of SLE. However, because the incidence rate of angioedema on SLE is low, doctors tend to unconsider the appropriate diagnosis management and administration on this breathing problem caused by SLE.Keywords: Systemic Lupus Erythematosus, angioedema, emergency AbstrakSistemic Lupus Eritematosus (SLE) adalah penyakit autoimun yang menyebabkan peradangan kronis dengan karakteristik pembentukan autoantibodi yang menyerang antigen. Penyakit ini dapat merusak organ multisistem, dan diagnosisnya hampir tidak diterapkan di Unit Gawat Darurat. Namun, kasus angioedema pada pasien SLE sangat jarang tidak hanya di Indonesia tetapi juga secara global. Artikel ini melaporkan kasus menarik dari wanita berusia 20 tahun yang datang ke Unit Gawat Darurat Rumah Sakit Siti Khodijah Sepanjang dengan keluhan bibir bengkak selama tiga hari. Keluhan dan pemeriksaan mengarah pada diagnosis SLE. Namun, karena tingkat kejadian angioedema pada SLE rendah, dokter cenderung tidak mempertimbangkan manajemen diagnosis yang tepat dan administrasi pada masalah pernapasan yang disebabkan oleh SLE ini.Kata kunci: Sistemik Lupus Eritematosus, angioedema, gawat darurat